Adopting a comprehensive approach to optimize medical education delivery in rural areas: A narrative review - Saurabh RamBihariLal Shrivastava; Prateek Sudhakar Bobhate; Prithvi Brahmanand Petkar; Vaishnavi H. Mishra (Journal of Clinical Sciences)
Medical education plays a pivotal role in ameliorating health-related outcomes by preparing health-care professionals with the desired knowledge, skills, and attitudes necessary to deliver effective patient-centered care. The purpose of the current review is to explore the role of medical education in rural areas, identify the potential challenges in the implementation, and propose suitable measures to overcome these challenges. The delivery of medical education in rural areas is expected to address the disparities in health-care delivery by serving people in underserved areas, thereby reducing the urban–rural divide. This is accomplished by ensuring timely access to medical services, resulting in the promotion of early diagnosis and better management of the disease. The process of delivery of medical education in rural settings has been associated with multiple challenges that must be systematically dealt with to improve the overall outcomes. In conclusion, promoting access to medical education in rural areas is a crucial step to establishing a robust and equitable health-care system that will aid in the attainment of universal health coverage. However, the need of the hour is to overcome the existing challenges to empower aspiring health-care professionals from rural backgrounds and also contribute to the overall health and well-being of underserved communities.